CONTEXT, TEXT, THEME AND STYLE IN THE CHAMAMAFILM OF THE HAUSA, NIGERIA (2014)
The CHAMAMA (CHAMAMA) is a sub-genre of the Hausa Kannywood Film which is popular among the Hausa in Nigeria because of its focus on rural lives and the Diaspora as a means of entertainment and correcting socials ills. Existing studies on the Hausa Film have concentrated on the sentimental genre which is mostly urban-centred to the neglect of CHAMAMA despite its predominant popularity and sociological significance. This study, therefore, examined the context, the text and style of CHAMAMA with a view to determining the extent of its sociological significance, and how its new roles broaden its positive impact on Hausa society. The study adopted structuralism, Baudry Apparatus and Maccabe theories of Film realism. The purposive sampling method was used in selecting twelve CHAMAMA Films- IbroyaauriBaturiya, IbroHonurable, IbroMinistantsaro, Ibrokawajo, Tsohon Dan Siyasa, Dan Auta a Lagos, Boko Zalla, Kwararre,DanBarewa, IbroDanfoDirebaDaushemaiadashigata, and IbroAloco. In-depth interviews were conducted with purposively selected 200 viewers of CHAMAMA in Kano, the centre of the Hausa Film culture, 50 artistes, 15 producers and 10 academics. Data were subjected to literary analysis and percentage scores. Three themes are identified in the selected Films: one each for politics and religion;one for economy, situated in the broad context of the Nigerian society and, specific context of public and private life. The economic theme, manifesting in relation to poverty, cuts across all the Films; political portrayal is dominant in IbroMinistanTsaro and IbroHonourable in which palpable irony and socio-economic contradistinction are used to depictabuse of power; and political subterfuge in Ibro Honourable which works on pedestrian logic and hyperboles. IbroAloco uses musical allegory and religious motifs to engage the theme of misconception and misrepresentation of Islamic doctrines, which often result in violent conflict among religious groups.The strength of CHAMAMA lies in the realistic depiction of the various changes taking place in contemporary Hausa society and the implications on the society. The Film is a deconstruction of contemporary Hausa society, in a way that reveals inherent institutional contradictions. About 85.0% of the producers believed that CHAMAMA was critically refractive and a potent medium of reaching the people. While 85.0% of the viewers affirmed the relevance and popularity of CHAMAMA, 15%, especially academics, believed that it did not demonstrate in-depth understanding of the problems associated with Hausa society, and that it was often simplistic in its interpretation of social problems. All the artistes affirmed the relevance of the Film but that its potential could be further broadened to include promotion of public health, skill development and agriculture programmes of the government. The context that evokes the themes of CHAMAMA is foregrounded in the Hausa world view that is well represented through subject and medium-constrained stylistic devices. In spite of its criticisms, CHAMAMA has remained a major sociological tool in Hausa society. Therefore, Government and society should give CHAMAMA the needed support to broaden its current scope for enhanced effectiveness.